Securing Web Application by Embedded Firewall at Gytech Indosantara Mandiri Ltd. - Yusup, Muhammad; Maisyaroh, Maisyaroh; Septiana, Laila (PIKSEL : Penelitian Ilmu Komputer Sistem Embedded and Logic, 2020)
Gytech Indosantara Mandiri Ltd. in the last few years experienced many Cybercrime attacks on the Web Server which caused many moral and material losses. Therefore, it is necessary to consider ways to fight and prevent attacks on the webserver. One way to fight and prevent attacks is to use the Attack Signatures method by using ModSecurity and fail2ban as a Web Application Firewall (WAF). ModSecurity is used to detect and prevent the occurrence of Cyber Crime in the Http and https services. Whereas Fail2ban is used to prevent Bruteforce attacks on ssh, FTP and telnet services. Modesecurity, which acts as a Web Application Firewall (WAF) will send logs to Fail2ban when exploits occur on the Web Server. Meanwhile, Fail2ban will block the Attacker's IP address so that both can be used as a Web Application Firewall or can be used as layer 7 network security.